« Xanny help the pain » : pistes pour une étude de la corrélation entre addiction et souffrance psychologique comme moteur esthétique de la scène emo rap - Fabrice Vergez (Transatlantica)
The aim of this paper is to suggest a few leads for a formal, cultural, and political study of the emo rap scene, and to start investigating some of these leads in more depth. We present a broad overview of the emo rap scene, which emerged on Soundcloud during the second half of the 2010s. We then move on to analyze the correlation between drug consumption and psychological pain that lays at the core of the scene’s aesthetic, by situating it in the context of the broader history of American rap and commenting upon the aesthetic strategies that represent the emotional effects of addiction and other mental health disorders in a few chosen examples.